ATP6V1B1 mutations in distal renal tubular acidosis and sensorineural hearing loss: clinical and genetic spectrum of five families. (7th August 2013) - Subasioglu Uzak, Asli; Cakar, Nilgun; Comak, Elif; Yalcinkaya, Fatos; Tekin, Mustafa
Abstract: Distal renal tubular acidosis (DRTA) is characterized by tubular defects in urinary acidification and hyperchloremic metabolic acidosis, hypokalemia, hypercalciuria, hypocitraturia, nephrocalcinosis and nephrolithiasis. Mutations in ATP6V1B1 cause DRTA associated with sensorineural hearing loss. The objective of this multicenter study is to screen DRTA patients with sensorineural hearing loss for ATP6V1B1 gene mutations and present genotype/phenotype correlation. Clinical data in five unrelated consanguineous families with DRTA and hearing loss were obtained in Turkey. For mutation screening, all coding exons of ATP6V1B1 were PCR-amplified and sequenced from genomic DNA. In our cohort of five families, there were four different homozygous ATP6V1B1 mutations in affected individuals: c.91C>T (p.R31X), c.232G>A (p.G78R), c.497delC (p.T166RfsX9) and c.1155dupC (p.I386HfsX56). Our study shows that rare and family-specific variants in ATP6V1B1 are responsible for DRTA and sensorineural hearing loss syndrome in Turkey. While firm genotype–phenotype correlations are not available, detailed clinical and molecular analyses provide data to be used in genetic counseling.